Production improvement with flow shop scheduling heuristics in Household utensils manufacturing company. Issue 1 (1st January 2018) - Wolde, Micheal G.; Berhan, Eshetie; Jilcha, Kassu
Abstract: This paper aimed at improving the production of a household utensils manufacturing company with flow shop scheduling heuristics. To achieve the planned production volume, a company needs to establish an optimal production sequences. A household utensils manufacturer in Ethiopia was our case company to investigate. We have studied the production sequence of a flat cooking pan, where one packed set of a flat cooking pan comprises seven diametrically ordered flat cook pans. Three production scenarios were developed based on the production line constraints of the case company. Among the various flow shop scheduling heuristics, Campbell, Dudek and Smith (CDC), and Nawaz, Enscor and Ham (NEH) methods were applied. In all production scenarios the applied heuristics yields an optimal production sequences with considerable reduction of a makespan. The optimal production sequences improved the annually planned production volumeby more than 22%. Moreover, the paper discusses the performance of the applied heuristics.